Evaluation of myocardial repolarization in patients with chronic renal failure - Alashimi, Abbas F.; Mohammed, Najeeb H.; Thamer, Ammar A. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Patients with chronic renal failure ( CRF) are at increased rick of cardiovascular diseases and 60 of cardiovascular mortality in CRF is attributed to sudden death.